2014
DOI: 10.1177/2047487314535117
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants improve vascular function in children conceived by assisted reproductive technologies: A randomized double-blind placebo-controlled trial

Abstract: Antioxidant administration to ART children improved NO bioavailability and vascular responsiveness in the systemic and pulmonary circulation. Collectively, these findings indicate that in young individuals ART-induced vascular dysfunction is subject to redox regulation and reversible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 40 publications
(59 reference statements)
1
25
0
3
Order By: Relevance
“…This favorable effect appears to be related, at least in part, to prevention of ART-induced epigenetic alterations of the regulation of the eNOS gene. There is evidence that ART-induced vascular dysfunction in humans may be related to a similar mechanism (22). We speculate that the modification of the culture media may allow the prevention of ART-induced premature atherosclerosis in humans.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…This favorable effect appears to be related, at least in part, to prevention of ART-induced epigenetic alterations of the regulation of the eNOS gene. There is evidence that ART-induced vascular dysfunction in humans may be related to a similar mechanism (22). We speculate that the modification of the culture media may allow the prevention of ART-induced premature atherosclerosis in humans.…”
Section: Discussionmentioning
confidence: 75%
“…Assisted reproductive technologies (ART) represent a recent important example of this problem, since ART induces vascular and cardiac dysfunction in children (26,33,34) and causes premature vascular aging and arterial hypertension that are associated with a shortened life span in mice (20). Consistent with observations in humans suggesting that decreased nitric oxide [nitrate/nitrite (NOx)] bioavailability contributes to vascular dysfunction in the offspring of ART (22), data in ART mice indicate that epigenetic alterations of the endothelial nitric oxide synthase (eNOS) gene that translate into decreased vascular eNOS expression and NOx synthesis underpin premature vascular aging and arterial hypertension (20). There is increasing evidence that suboptimal embryo culture conditions contribute to ART-induced epigenetic alterations (6,12,15), as evidenced, for example, by the fact that current culture media used for ART are unable to maintain genomic imprinting of in vitro embryos (15).…”
Section: Assisted Reproductive Technologies-induced Cardiovascular Dymentioning
confidence: 68%
“…These alterations also appear to play a role in humans; in a recent study, we showed that 4-week daily oral administration of antioxidant vitamins C and E increased plasma NO bioavailability, normalized FMD and attenuated hypoxic pulmonary vasoconstriction at high altitude in ART children but had no detectable eff ect on control children [74].…”
Section: Role Of Epigenetic Mechanisms In Art-induced Alteration Of Tmentioning
confidence: 84%
“…Therefore, we evaluated the endothelial function using the FMD jointly to the EndoPAT technology (Fig. 3), only in one study center-Bern University Hospital, Switzerland, with large prior experience with this methodology (28)(29)(30)(31). Description of technical procedure is reported in the Suppl.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%